Sequential changes in cerebral blood flow in patients with hypertensive subcortical intracerebral hematoma - Nakamura, Saburo; Yoshida, Kenshi (Japanese Journal of Stroke, 1996)
Sequential changes in cerebral blood flow (CBF) were investigated in patients with surgicallyevacuated hypertensive intracerebral hematoma (ICH). The subjects comprised 14 patients with subcortical ICH. CBF was studied by means of stable xenon-enhanced computed tomography (xenon CT) before and after surgery, and during the chronic stage. The pre-operative CBF and its response to acetazolamide (AZ) on the hematoma side declined in accordance with an increase in hematoma volune. Not only the global CBF levels on the hematoma side but also the regional CBF surrounding the hematoma were distinctly improved after evacuation of the hematoma in all cases. These findigns suggest that surgical evacuation, in cases of hypertensive subcortical hematoma, might be useful for improving the CBF.